2013
DOI: 10.1002/jnr.23242
|View full text |Cite
|
Sign up to set email alerts
|

Microglia express distinct M1 and M2 phenotypic markers in the postnatal and adult central nervous system in male and female mice

Abstract: Although microglial activation is associated with all CNS disorders, many of which are sexually dimorphic or age-dependent, little is known about whether microglial basal gene expression is altered with age in the healthy CNS or if it is sex-dependent. Analysis of microglia from the brains of 3 day (P3) - to 12 month-old male and female C57Bl/6 mice revealed distinct gene expression profiles during postnatal development that differ significantly from adulthood. Microglia at P3 are characterized by relatively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
259
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(283 citation statements)
references
References 50 publications
10
259
1
3
Order By: Relevance
“…We observed that inflammatory proteins are present and detectable in the healthy cortex, however, the concentration of these proteins were similar among sex groups in adult mice. Similarly, a previous investigation determined that mRNA levels of VEGF, arginase, and IL10 measured from primary microglia collected from 4 month old male mice were similar between males and females (Crain et al, 2013). Based on these data, we surmise that neuroinflammatory protein concentrations have a minimal influence on observed differences in microglia morphology and CR3 in the cortex.…”
Section: Discussionsupporting
confidence: 75%
“…We observed that inflammatory proteins are present and detectable in the healthy cortex, however, the concentration of these proteins were similar among sex groups in adult mice. Similarly, a previous investigation determined that mRNA levels of VEGF, arginase, and IL10 measured from primary microglia collected from 4 month old male mice were similar between males and females (Crain et al, 2013). Based on these data, we surmise that neuroinflammatory protein concentrations have a minimal influence on observed differences in microglia morphology and CR3 in the cortex.…”
Section: Discussionsupporting
confidence: 75%
“…Macrophages have been classified as either M1 or M2, with activated M1 macrophages having proinflammatory, antimicrobial phenotypes and M2 macrophages having anti-inflammatory, wound-healing phenotypes (reviewed in reference 45). It is now appreciated that even this dichotomy does not capture the full continuum of macrophage phenotypes (47) and that additional macrophage diversity is generated from the complex signaling environment (47) and from inherent differences, such as basal gene expression (48), that alter how cells respond to signals. Together, cellular ontogeny, signaling environment, activation state, and basal gene expression generate diverse macrophage populations capable of performing a variety of functions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms can lead to motor neuron injury, which funnel into a final pathway or noncell-autonomous toxicity and neuroinflammation leading to motor neuron death [59][60][61][62][63]. In contrast, M2 produce high levels of antiinflammatory cytokines and neurotrophic factors including IL-4, IL-10, and insulin-like growth factor (IGF)-1 in addition other neruoprotection signals such as CD200 and fractalkine [51,60,[64][65][66][67][68].…”
Section: Microgliamentioning
confidence: 99%